Estudio bibliográfico sobre estrategias de enseñanza de la lectoescritura en los estudiantes con discapacidad intelectual del subnivel 2 de educación general básica del ecuador, periodo 2010-2020 - Pineda Torres, Jinmy Sebastián (2021)
The present research work arose with the objective of examining, through bibliographic analysis, the incidence of teaching strategies for reading and writing in students with intellectual disabilities in sub-level 2 of basic general education, with research done during the period 2010-2020 in Ecuador, It is of descriptive type, with a nonexperimental field design and with a mixed approach, making use of scientific, qualitative, quantitative, analytical-synthetic, deductive and descriptive methods, with a sample constituted by 17 investigations that are distributed as follows: 5 investigations of Strategies for teaching reading and writing, 8 papers on the methods of reading and writing, and 4 publications of the difficulties in reading and writing in students with intellectual disabilities. The results describe that the use of traditional methods prevents a better development of literacy skills. As a main conclusion, it was possible to examine that the use of memoristic strategies and methods do not benefit learning as much as those methods that take into account the particularities, potentialities and contexts where the student is immersed, which is why María Troncoso & del Cerro's method is a good alternative to traditional methods. The research allowed the elaboration of a guide of strategies for teaching reading and writing to students with intellectual disabilities, which addresses the Troncoso method as a sequential and gradual teaching strategy for reading and writing.